Informal social ties and relationship orientation in Korean business exchanges: A content analysis of ten inter-organizational research collaborations - Martin Hemmert; Jae-Jin Kim (University of Duisburg-Essen, Institute of East Asian Studies (IN-EAST), 2018)
We examine the role of informal social ties and of relationship orientation in two types of inter-organizational research collaborations in South Korea: new product development (NPD) collaborations and university-industry research collaborations (UICs). An in-depth content analysis of five NPD collaborations and five UICs reveals that whereas both informal social ties and relationship orientation are prevalent in research collaborations in Korea, they play different roles for relationship quality and collaboration outcomes. Informal social ties strongly vary in their types and strength, and enhance relationship quality and outcomes only when they are well-aligned with the task-specific requirements for a given collaboration. Relationship orientation manifests itself both in task-related and social exchanges between collaboration partners. A strong relationship resulting from such exchanges often enhances outcomes such as knowledge acquisition and business performance.
Keywords: 330; inter-organizational research collaboration; informal social ties; relationship orientation; relationship quality; knowledge acquisition; Korea